Let's solve the equation step by step.
Given: \[ 14(x + 3) = 5 \]
Step 1: Distribute the 14.
- \(14\) is multiplied by \((x + 3)\).
- \(14(x + 3) = 5\) remains unchanged.
So the answer is:
- (multiply) \(14\)14(x+3)=5
- \(14\)
Step 2: Divide both sides by 14. \[ x + 3 = \frac{5}{14} \]
So, the answer is:
- \(x + 3 = \frac{5}{14}\)
Step 3: Subtract 3 from both sides. \[ x = \frac{5}{14} - 3 \]
So, the answer is:
- Subtract \(3\) from both sides.
Step 4: Now subtract \(3\) (which can be written as \(\frac{42}{14}\)) from \(\frac{5}{14}\): \[ x = \frac{5}{14} - \frac{42}{14} \] \[ x = \frac{5 - 42}{14} \] \[ x = \frac{-37}{14} \]
So, the answer is:
- \(x = \frac{-37}{14}\)
Putting it all together, here are the filled-in steps:
- (multiply) \(14\)14(x+3)=5
- \(14\)
- Subtract \(3\) from both sides.
- \(x = \frac{-37}{14}\)